Analisis Kualitas Sepatu Lokal Compass - Muhammad Ridho Dhiaz; Rana Rana; Syamsul Hidayat (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
This study aims to analyze the quality of Compass shoes based on material, design, comfort, and durability. Compass shoes, as one of the increasingly popular local brands in Indonesia, have attracted consumer attention, especially among young people. The research method involved surveys of 100 respondents who use Compass shoes and laboratory tests on the materials and construction of the shoes. The results show that the material quality of Compass shoes falls into the good category, with high durability for daily use. In terms of design, Compass shoes received positive feedback for their modern appearance and alignment with current trends. However, there were some complaints regarding comfort, particularly for users with high activity levels. The shoes’ durability also received favorable evaluations, especially for use in urban environments. Overall, Compass shoes can compete with other local brands, but improvements in comfort are necessary to attract a broader market segment. This study is expected to serve as a reference for Compass shoe manufacturers in enhancing product quality and provide relevant information for consumers in selecting quality local products.